Cognition of ourselves through cognition of the culture of our ethnic group - Bakhtikireeva, Uldanai M.; Shagimgereyeva, Bakytgul E.; Amalbekova, Maral B. (The New Research of Tuva, 2023)
The article provides a review of the monograph "Tuvans: Native People" (St. Petersburg: Nestor-Istoriya, 2022). Its authors, ethnic Tuvan women (Ch. K. Lamazhaa, N. D. Suvandii, Sh. Yu. Kuzhuget, Sh. B. Mainy), have dedicated their work to comprehending and delineating the culture intimately linked to them through birthright, linguistic communication, and inseparable cohabitation. The authors of this review, ethnic Kazakh women, contemplate the monographic exploration encapsulated within the linguistic confines of the Russian language by ethnic Tuvan women, particularly focusing on their compelling authorial subjectivity. What characterizes the nature of such authorial positioning within the monograph? How does their methodology differ from the perspectives of their colleagues who share Tuvan origins? The accentuated subjectivity of the authors has led to the formulation of their unique concept — the thesaurus approach, which they label as the Russian iteration of Indigenous Methodology. From this emphatically articulated epistemological stance, the scholars scrutinize antecedent outsider and insider research methodologies concerning the study of Tuvan culture and its genesis. They delve into the essence of pivotal concepts constituting the “nucleus” of the Tuvan cultural repository: ög, kuda, urug-daryg, mal, all subsumed under a unified, clan-based concept — tөrel. Drawing from their perspective, Tuvan colleagues draw a crucial inference, one pertinent to researchers from diverse indigenous communities within the Russian Federation and the Central Asian region: Tuvan culture fundamentally rests upon the framework of kinship ties. In the process of dissecting the monograph authored by Tuvan scholars, an overarching objective crystallizes for each insider scholar — to introspectively comprehend themselves. To shift the focus from the object of study to themselves as subjects, unwilling to perpetuate the role of “victims” in relation to the “metropolis”, a convenient posture that absolves them from accountability for the state of their people’s culture and the academic discipline devoted to it.